2009
DOI: 10.4314/ajbr.v9i3.48914
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical changes in serum of Rat treated with aqueous extract of the fruit of Telfairia occidentalis

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 4 publications
(1 reference statement)
1
1
0
Order By: Relevance
“…Therefore, from the results obtained so far, it could be inferred that the fruit mesocarp may not only be ineffective in ameliorating or improving anaemic conditions due to the absence of key minerals and vitamins necessary to mediate this action but might also tend to worsen the case in a diseased condition. These findings seem to be in keeping with the research of Eseyin et al [ 13 ], where it was suggested that the fruit extract may be unsafe for consumption due to its damaging effects on the rat liver and bones.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore, from the results obtained so far, it could be inferred that the fruit mesocarp may not only be ineffective in ameliorating or improving anaemic conditions due to the absence of key minerals and vitamins necessary to mediate this action but might also tend to worsen the case in a diseased condition. These findings seem to be in keeping with the research of Eseyin et al [ 13 ], where it was suggested that the fruit extract may be unsafe for consumption due to its damaging effects on the rat liver and bones.…”
Section: Discussionsupporting
confidence: 92%
“… Diagram of the cross-sectional area of T. occidentalis , showing the exposed fruit mesocarp (yellow part), leaves, flowers, and seeds [ 13 ]. …”
Section: Figurementioning
confidence: 99%